Problems of accounting methods in credit unions as non-bank financial intermediary and their solutions - V.S. Mokhniak; L.M. Pylypenko (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
According to the results of the study, it was argued that the main problems of the accounting methodology in credit unions are due to the need to apply accounting and reporting standards intended for commercial enterprises, while credit unions are non-profitable financial institutions. It is determined that mostly this problem concerns about the accounting for equity of credit unions. The article substantiates the expediency of reflecting in the balance of membership dues of members of credit unions precisely as components of equity. The classification and characteristics of capital reserves and cash reserves of credit unions aimed at ensuring the appropriate level of their financial stability are given. Recommendations on improving the analytical accounting of these reserves in accordance with their purpose and the requirements of regulatory documents governing the systematization of accounting accounts are presented. Despite the fact that the activities of credit unions as non-bank financial intermediaries are subject to rather strict legislative regulation, the accounting methodology for the main business operations i.e. attracting deposits and issuing loans, is not sufficiently disclosed in peremptory documents. The article provides a classification of loans and deposits to deposit accounts of members of credit unions. Forms of analytical accounting of contributions to deposit accounts of members of credit unions and loans issued by them are proposed, which make it possible to conduct analytical accounting for each debtor and creditor, and also form an information base for monitoring timely and full repayment of debts on loans and attracted deposits.